EKOFEMINISME DALAM PENGELOLAAN AIR BERSIH DI DUSUN TINJALAS, DESA SERAYA TIMUR: REPRESENTASI KEADILAN LINGKUNGAN DAN KESETARAAN GENDER - I Made Mardika; Anak Agung Ayu Dewi Larantika; Leoneto Madeira Martins (Kulturistik: Jurnal Ilmu Bahasa dan Budaya, 2026)
This study aims to analyze ecofeminist discourse in representing environmental justice and gender equality in clean water management in impoverished rural areas of Bali Province, with a particular focus on the role of women in sustaining water resources. The study employed a qualitative descriptive approach based on contemporary ecofeminist theory. The research was conducted in Tinjalas Hamlet, Seraya Village, Bali, involving a sample of 20 households selected through simple random sampling. Data were collected through structured and focused group interviews as well as non-participant observation and were analyzed using qualitative descriptive methods. The findings reveal that women play a dominant role in accessing, utilizing, and managing clean water efficiently, including collecting water from springs and rivers and harvesting rainwater as an adaptive strategy to cope with limited water availability. Men's participation in these activities is relatively low, although gender relations within the family do not exhibit significant conflict or dichotomy. Women also demonstrate strong ecological awareness by using water wisely, maintaining environmental cleanliness, and treating water to make it safe for consumption in order to prevent waterborne diseases. These findings confirm that women make a strategic contribution to promoting environmental justice and ensuring the sustainability of clean water management in impoverished rural communities.